2020
DOI: 10.1177/2050312120910353
|View full text |Cite
|
Sign up to set email alerts
|

Venoarterial extracorporeal membrane oxygenation in heart surgery post-operative pediatric patients: A retrospective study at Christus Muguerza Hospital, Monterrey, Mexico

Abstract: Objectives: Extracorporeal membrane oxygenation is a life support procedure developed to offer cardiorespiratory support when conventional therapies have failed. The purpose of this study is to describe the findings during the first years using venoarterial extracorporeal membrane oxygenation in pediatric patients after cardiovascular surgery at Christus Muguerza High Specialty Hospital in Monterrey, Mexico. Methods: This is a retrospective, observational, and descriptive study. The files of congenital heart s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…One hundred and three studies were excluded after full-text evaluation. Eventually, this systematic review was based on 43 studies, encompassing 38 case series ( 11 48 ) and 5 case-controlled studies ( 49 – 53 ). A flowchart depicting the search strategy is shown in the Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and three studies were excluded after full-text evaluation. Eventually, this systematic review was based on 43 studies, encompassing 38 case series ( 11 48 ) and 5 case-controlled studies ( 49 – 53 ). A flowchart depicting the search strategy is shown in the Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Bridging to heart transplant was reported in seven studies ( 12 , 13 , 27 , 31 , 34 , 35 , 53 ), while a subsequent ventricular assist device (VAD) implantation was only reported in one study ( 50 ). A total of 11 studies ( 12 , 14 , 16 , 23 , 24 , 26 , 36 , 38 , 44 , 45 , 48 ) reported the causes to in-hospital mortality, which was mainly caused by MODS, infections, and ventricular failure.…”
Section: Resultsmentioning
confidence: 99%
“…We further excluded 42 studies after full‐text evaluation, because they did not meet inclusion criteria. Eventually, 28 studies 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 were amenable to meta‐analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our meta‐analysis, applying a random‐effects model, the pooled short‐term mortality (28 studies,1736 patients) was 45.6% (95% CI, 38.7%–52.4%) (Figure 2 ). 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 There was no evidence for publication bias because of the funnel plot appearing visually symmetrical (Figure 3 ), and the Egger test suggesting insignificant difference for our primary outcome of interest ( P egger =0.23). The sensitivity analysis performed by excluding the studies with a Joanna Briggs Institute score <8, showed that the pooled short‐term mortality was 46.2% (95% CI, 39.0%–53.4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation